Performance characteristics of selected/deselected under 11 players from a professional youth football academy - Platvoet, S. W.; Opstoel, K.; Pion, J.; Elferink-Gemser, M. T.; Visscher, C. (International Journal of Sports Science & Coaching, 2020)
This study aimed to determine whether players selected for the under 11 team of a professional youth football academy outperform their deselected peers in physical, technical and gross motor coordination skills, or in psycho-social capacities. Of the young players active at different amateur clubs yearly 2% were scouted to participate at trainings and matches from an academy before the first objective baseline testing (season 1 n = 54 boys, season 2 n = 49, age: 9.25 ± 0.46). Most of the scouted players (n = 103) were born in the first quarter of the year (47.6%) and started playing football at a young age (4.80 ± 0.84). Mann-Whitney U tests showed that the selected under 11 players (n = 31) from the reduced pool outperformed their deselected peers (n = 72) in the 30-m slalom sprint, dribble test and Loughborough soccer passing test, and on sport learning-, motor-, creative- and interpersonal capacity (P < 0.05). A discriminant analysis resulted in a significant discriminant function (Wilks` = 0.673, df = 16 and P = 0.002) with 69.6% of players classified correctly. In sum, the current system, tends to scout 9-year old soccer players with multiple years of soccer experience, and well-developed motor skills, who are predominantly born in the first quarter of the year. Of those players, the ones with better physical and technical skills, who are believed to have most potential to become elite in the future are selected. However, 25 of the players with a high probability of being selected were deselected. Whether this system is appropriate serves a broader ethical discussion within contemporary society.